Prevalence and factors associated with disruptive behavior among Iranian students during 2015: a cross-sectional study - Araban, Marzieh (Ital J Pediatr, 2020)
BACKGROUND: Disruptive behavior can have lifetime consequences for youth. Prevention, early identification and treatment of disruptive behavior can improve outcomes for these youth. The purpose of the present study was to assess the prevalence of disruptive behavior among a sample of Iranian youth, and the relationship of disruptive behavior to other psychological phenomena that may be targeted for prevention, early identification and treatment. METHOD: The sample consisted of 600 high school students (300 boys and 300 girls; ages 15 to 18 years old) selected through multi-stage random sampling in Saveh city, of Iran, in 2015. Questionnaires assessed several phenomena including demographics, life satisfaction, social support, depression, stress, smoking and hopefulness. The Disruptive Behavior Scale was also utilized. Univariate analyses were followed by multiple logistic regressions to examine relations among disruptive behavior and other constructs. RESULTS: Prevalence of disruptive behavior was 7.5%, in boys and 3.1%, in girls. Mean scores were 22.97 ± 1.17 for boys and 19.15 ± 1.06 for girls, with a significant difference between them (P < 0.05). The results of regression revealed low life satisfaction (OR = 3.75; 95% CI: (2.37–5.91), social support (OR = 0.72; 95% CI: (0.56–0.82) and hopefulness (OR = 0.85; 95% CI: (0.62–0.92); and smoking (OR = 3.65; 95% CI: (2.19–6.06), being male (OR = 2.55; 95% CI: (1.54–4.22), and higher stress (OR = 1.92; 95% CI: (1.60–2.91) and depression (OR = 2.76; 95% CI: (1.82–4.88) were significant factors in predicting disruptive behavior. CONCLUSION: Disruptive behavior was associted with life satisfaction, smoking, being a boy, social support, hopefulness, stress, and depression. Targeting constructs (e.g., support, stress) associated with disruptive behavior may assist in prevention, early identification and treatment of problem behavior. For example, health promotion programs to increase hopefulness, satisfaction and support, and reduce stress, depression and smoking might be of importance for prevention and treatment of disruptive behavior.